2020
DOI: 10.1111/1365-2664.13575
|View full text |Cite
|
Sign up to set email alerts
|

Escape responses of terrestrial and aquatic birds to drones: Towards a code of practice to minimize disturbance

Abstract: Advances in human technology can lead to widespread and rapid increases in interactions between wildlife and potentially disturbing stimuli. The recreational use of drones is widespread and increasing, yet laws and codes of practice which aim to manage deleterious impacts (e.g. negative interactions with wildlife) are reactionary, unscientific and inadequate. One prominent potential negative effect of drones interacting with birds is disturbance; the disruption of normal states caused by responses such as esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
70
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 35 publications
7
70
0
4
Order By: Relevance
“…However, the use of drones for research purposes should always be carefully evaluated. Studies using these vehicles must avoid any risk of death or physical damage for birds either by accidental collisions or deliberate attacks, and should minimize the disturbance or alteration of birds´ behavior that would result in nest failure (Weston et al., 2020). These conditions must be observed for any research involving drones but especially when species of conservation concern are targeted in the study.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of drones for research purposes should always be carefully evaluated. Studies using these vehicles must avoid any risk of death or physical damage for birds either by accidental collisions or deliberate attacks, and should minimize the disturbance or alteration of birds´ behavior that would result in nest failure (Weston et al., 2020). These conditions must be observed for any research involving drones but especially when species of conservation concern are targeted in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Although internet reports on drone-wildlife interactions have been growing exponentially since 2012 (see Fig. 1 in 11 ), by 2018 only 30 articles recording drone effects on wildlife were published, and of these only 50% were actually designed to detect such impacts 10 . The information to date comes mostly from studies on birds and marine mammals, which initially suggested that disturbance was unlikely or imperceptible 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Weimerskirch et al (2018) noted significant approach distance effects, with distances <10 m provoking responses in the majority of breeding Antarctic bird species studied, whilst Bevan et al (2018) noted a direction of approach effect with vertical approaches the most likely to result in disturbance at a colony of breeding crested tern (Thalasseus bergii). Work by Weston et al (2020) identified not only approach distance but also proximity of take-off location as a key factor in the response of a species. Whilst work by McEvoy et al (2016) also identified the shape of the UAV (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Weston et al. (2020) identified not only approach distance but also proximity of take‐off location as a key factor in the response of a species. Whilst work by McEvoy et al.…”
Section: Introductionmentioning
confidence: 99%